(3LhGH eSCdI SCdgG GdWhSis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3eMeO Hf GdWGgQ s)
(3ChdgG (B:s
(3CYde Cf eHGMK EfYcGS GdTYGYGJ hEfYWGagG eHfjg Ydi ebOeGJ s
(3BNQgG (B:s
(3EdG Ydi ehVhY hGMO eYjf dcd hGMO efgG jchf Pdc GdehVhY Ydi hVY NGU ef fYje GdTYGY hPdc eG CQOfGg JeJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3eUOQ GbJfGA GdCUd (B:s
(3CjI Gddg GdMcje GdYGeg (B_ (3GdfLa (B(285) s
Keywords: (3GdQjGVjGJs